Miradas sanitarias en torno a las mujeres bolivianas en Argentina: Un aporte desde la interseccionalidad - Aizenberg, Lila (2019)
This article analyzes the perceptions of health teams concerning Bolivian migrant women in the provinces of Córdoba and Mendoza, Argentina. The research consisted on a qualitative, exploratory-descriptive study based on semi-structured interviews. From the intersectionality theory it analyzes how health professionals construct the culture of the other in relation to Bolivian migrant women’s health and the way in which the later influences health care. It shows the “cultural reductionism” that characterizes the perceptions of health teams as well as the different forms of social domination behind the reproduction of sanitary inequalities.